Parthenolide Attenuates Sepsis-Induced Acute Kidney Injury in Rats by Reducing Inflammation. (6th January 2023) - Shou, Di-Wen; Li, Yi-Rong; Xu, Xiu-Juan; Dai, Mu-Hua; Zhang, Wei; Yang, Xue; Tu, Yue-Xing
Abstract : Background . Sepsis is a common complication of severe trauma, burns, infection, or major surgery. This disease-related end-organ dysfunction results from systemic inflammatory response syndrome (SIRS). Acute kidney damage (AKI), also known as acute renal failure, is one of the most frequent and serious sequelae of sepsis. Nuclear transcription factor- κ B (NF- κ B) regulates the transcription of inflammation-related genes and operates as a mediator in the immune system. While parthenolide (PTL) has been reported to prevent harmful inflammatory reactions, its effects on sepsis-associated AKI are unknown. The current study investigates the effects of PTL in sepsis-associated AKI using cell and cecal ligation and puncture (CLP) models. Methods . Lipopolysaccharide (LPS)-stimulated rat glomerular mesangial cells were treated with 10 μ M PTL. Inflammatory mediators, including TNF- α, IL-6, and IL-1 β, in the culture supernatants were measured by ELISA, and NF- κ B levels were assessed by qPCR. After the generation of the septic CLP model, rats were intraperitoneally injected with 500 g/kg PTL and were euthanized after 72 h. Serum and kidney samples were analyzed. Results . TNF- α, IL-1 β, and IL-6 levels were elevated after LPS treatment of rat glomerular mesangial cells (p = 0.004, p = 0.002, and p = 0.004, respectively) but were significantly reduced in the PTL treatment group (p ≤ 0.001, p = 0.01, and p ≤ 0.001 ). NF- κ B p65 levels were also increased after LPS treatment in this group and were reduced in the PTL treatment group. PTL treatment also reduced kidney damage after CLP induction, as shown by histological analysis and reductions in the levels of BUN, Cre, KIM-1, and NAGL. CLP-induced kidney inflammation together with increased levels of proinflammatory cytokines and inflammatory-related proteins. The elevated levels of renal TNF- α, IL-6, and IL-1 β were downregulated after PTL treatment. The PTL treatment also reduced the CLP-induced activation of NF- κ B p65 in the damaged kidneys. Conclusion . PTL reduced inflammation induced by CLP-induced AKI in rat models and LPS-induced damage to glomerular mesangial cells by suppressing NF- κ B signaling.